APLIKASI FMA DAN PUPUK KANDANG TERHADAP PRODUKSI DAN KUALITAS RUMPUT GAJAH (Pennisetum purpureum Schum) - Khalidin, -; Mirza, Iskandar; Azis, Abdul (Pastura; Vol 3 No 1DO - 10.24843/Pastura.2013.v03.i01.p05)
The objectives of the study were to evaluate effects of arbuscular mycorrhiza fungi (AMF) and manure on production and quality of the elephant grass. The experiment used a factorial randomized completely block design, consisting of two factors: AMF and manure, with three replications. AMF consisted of two levels, i.e. without AMF and with AMF 10 g hole-1, while manure consisted of 0, 15, 30, and 45 tons ha-1. Results showedthat the best combination for crude proteinandcrude fibergrass at age of 50 days after planting was found at without AMF and 15tons ha-1of animal manure. Manure of45 tonsha-1produced higher elephantgrass production than that of30tons ha-1, 15tons ha-1, andwithoutmanure.
Keywords: arbuscular mycorrhizal fungi, manure, elephant grass.